Italian Culture and Art Representations in Odesa under the Policy of Romanization Conditions (1941–1944) - Batsak, Kostyantyn (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2024)
Relevance of the study. Italian culture and art in Odesa, their influence on the city development, the European traditions diffusion in urban planning, education, music and theatre activities have a century-long history. It was interrupted with the World War the First and, subsequently, with decades of the bolsheviks’ dictatorship. Therefore, although brief-lasted, Odessa involvement in the cultural space of Italy during the Romanian occupation of the city in 1941–1944, which took place in Hitler’s and Mussolini’s ideological paradigm of the «new Europe» possessions, became a unique experience of the urban culture traditions revival — primarily, the Italian musical and theatre and instrumental performing arts representation. The purpose of the article is to investigate the forms of Italian culture and art representation in Odesa in the context of the Royal Romania occupation policy implementation, aimed at city population integration into the system of the «Roman world» ideological values under the fascist Italy hegemony. Methodology. The methodological background is due to the interdisciplinary nature of the investigation. The scientific toolkit consists of methods that ensure the reliability of the obtained results and conclusions: source studies (to study the narrative sources, newspaper reports); historical and biographical (to investigate the unknown and little-known Italian artists’ biographies pages and their facts clarification); comparison method (used for the purpose of information contained in documents of personal origin, submitted in newspaper reports, studied in scientific investigations verification); historical-systemic method (to investigate the Romania adaptation model of cultural policy and its changes under Odesa development historical features influence); method of generalization (to reveal the Kingdom of Italy representative institutions cultural and propaganda policy in the city essential characteristics). Results and conclusions. Little-known aspects of Odesa cultural and artistic life during the Romanian occupation of 1941–1944, when the city functioned as Governorate of Transnistria administrative centre, were investigated. In particular, the forms of Italian culture and art representation in the context of the Romanization policy implementation have been identified and described. That policy is proved being the processes of Romanianization component, was implemented by the occupying power exclusively in the field of culture in order to promote «European values», «new European culture», represented by Nazi Germany, fascist Italy and royal Romania. The policy of Romanization is revealed to be implemented with the Italian Royal Bureau, later the Italian Institute of Culture in Odesa involvement, by popularizing the Italian language and culture, cinematography, visual and musical arts. The local intelligentsia, including ethnic Italians and their descendants who survived in the Stalinist repressions conditions are shown as the social group targeted by this policy. In practice, that policy was embodied in the Odesa Art Museum exposition designing, the Odesa Opera and Ballet Theatre repertoire, the Italian language and culture courses deployment, Italian art films and newsreels demonstration, Italian singers and musicians invitation to take part at the local stage performances and to work as conservatory professors. On the basis of the city occupation newspapers publications and diary entries of contemporaries, the influence of representatives of the Italian musical environment occupied Odesa cultural life is shown. In particular, the world-famous singers and musicians such as tenor Tito Schipa’s, singer and film actress Katerina Boratto’s, orchestra conductor Molinari Francesco Pradelli’s, cellist Antonio Yanigro’s, harpist Luigi Magistretti’s scenic activities in the city are highlighted, also the violinist Carlo Felice Chillario’s concert practice and pedagogical efforts are investigated.